2022
DOI: 10.7554/elife.71802
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetic scores for the circulating proteome as tools for disease prediction

Abstract: Protein biomarkers have been identified across many age-related morbidities. However, characterising epigenetic influences could further inform disease predictions. Here, we leverage epigenome-wide data to study links between the DNAm signatures of the circulating proteome and incident diseases. Using data from four cohorts, we trained and tested epigenetic scores (EpiScores) for 953 plasma proteins, identifying 109 scores that explained between 1% and 58% of the variance in protein levels after adjusting for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 81 publications
2
79
0
Order By: Relevance
“…Additionally, the DNAm signatures of proteins we quantify represent widespread differences across blood cells that are related to circulating protein levels and are therefore not derived from the same cell-types as proteins. Despite this limitation, previous work supports DNAm scores for proteins as useful markers of brain health, suggesting there is merit in integrating DNAm signatures of protein levels in disease stratification 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the DNAm signatures of proteins we quantify represent widespread differences across blood cells that are related to circulating protein levels and are therefore not derived from the same cell-types as proteins. Despite this limitation, previous work supports DNAm scores for proteins as useful markers of brain health, suggesting there is merit in integrating DNAm signatures of protein levels in disease stratification 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, DNAm accounts for inter-individual variability in circulating protein levels 14 16 . Recently, through integration of DNAm and protein data, we have shown that epigenetic scores for plasma protein levels—known as EpiScores—associate with brain morphology and cognitive ageing markers 17 and predict the onset of neurological diseases 18 . These studies highlight that while datasets that allow for integration of proteomic, epigenetic and phenotypic information are rarely-available, they hold potential to advance risk stratification.…”
Section: Introductionmentioning
confidence: 99%
“…DNAm can precisely track ageing through predictors termed “epigenetic clocks” [ 2 8 ]. DNAm has also been found to capture other components of health, such as smoking status [ 9 , 10 ], alcohol consumption [ 11 , 12 ], obesity [ 11 , 13 ], and protein levels [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…We developed a combined score, DNAmCVDscore , predictive of future CVD events by regressing the time-to-CVD event on 60 candidate DNAm surrogates: the nine newly developed within this study, 32 DNAm surrogates for blood measured (mainly inflammatory) proteins produced by Gadd and colleagues [ 23 , 26 ]; three epigenetic clocks (HorvathDNAmAge, HannumDNAmAgem, and DNAmPhenoAge) [ 20 ]; two DNAm surrogates for lead exposure [ 22 ]; six ‘Houseman’ DNAm surrogates for white blood cell (WBC) proportion [ 38 ]; and the nine components of the DNAmGrimAge clock (DNAm surrogates for smoking pack-years, telomere length, and seven blood measured proteins) [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…The best performing epigenetic clock, called DNAGrimAge, incorporates DNAm scores for seven circulating proteins and smoking pack-years, and it has been consistently associated with longevity and numerous age-related diseases, and functional and cognitive outcomes [ 11 , 19 , 21 ]. Other examples of DNAm surrogate of exposures and risk factors include the DNAm biomarkers identified by Colicino and colleagues for cumulative lead exposure [ 22 ], the one derived by Marioni and colleagues for several longevity-related and inflammatory proteins [ 23 26 ], the classification by Guida and colleagues of current, former (including time since smoking cessation) and never smokers based on blood DNAm biomarkers [ 7 ], and the recent characterisation of electronic health records phenotypes by Thompson and colleagues [ 27 ].…”
Section: Introductionmentioning
confidence: 99%